Influência da atmosfera gasosa e da fonte protéica sobre o desenvolvimento embrionário in vitro e taxa de prenhez em bovinos - Leivas, Fábio Gallas (2006)
The embryonic development and pregnancy rates are influenced by variations in embryo in vitro production (IVP) systems and protocols for bovine embryos, such as gaseous atmosphere, culture media and the protein supply adopted in the different steps of IVP. Two studies were performed to evaluate the effect of O2 tension on in vitro maturation (IVM) and fertilization (IVF) of bovine oocytes, and the protein supply in the embryonic in vitro culture. Immature Cumulusoocytes complexes (COC) were recovered by transvaginal ultrasound guided follicular aspiration (OPU) from Bos taurus indicus donors from commercial programs and randomly assigned according to the number and quality of the COC. Standard bovine IVM procedure was carried out in modified TCM-199, added of FSH, LH, Oestradiol, EGF, insulin and 10% bovine fetal serum (FCS), for 24h. Frozen semen was selected by Percoll gradient (90, 60 and 30%). The insemination was performed with 2x106 spermatozoa/mL in Fert-Talp with heparin and PHE, for 18 to 22h. Presumptive zygotes were in vitro cultured (IVC) in SOFaaci during 6 to 9 days with 5%CO2, 5%O2 and 90% N2 in air. All steps of IVC were performed in an incubator at 39ºC with satured humidity. The cleavage and blastocyst rates were analysed by GLM procedure. Hatching, quality I blastocyst and pregnancy rates were compared by Chi-square Test with 5% of significance. In experiment I (11 replicates) IVM and IVF of COC (n=1092) were conducted under 5% CO2 (20% O2) in air or in 5%CO2, 5%O2 and 90% N2 (5%O2). Experiment II was divided in two steps (IIa and IIb). In experiment IIa (n=1745 COC), the IVM and IVF was followed by in vitro culture (IVC) in SOFaaci added of 4mg/mL bovine serum albumin (BSA) or 4mg/mL BSA+2% bovine fetal serum (BSA+FCS). In experiment IIb (n=704 COC), after standard IVM and IVF, IVC was performed in the two media of Experiment IIa (BSA and BSA+FCS) and in a third group the SOFaaci was added of 4mg/mL BSA+2% FCS (BSA+FCSD4) on day 4 of IVC. The viability was accessed by morphological evaluation in D2 (cleavage), D7 (blastocysts and quality categories), D9 (hatched blastocysts), D45 (experiment I) and D60 (experiment II; pregnancy rates), considering day zero (D0) as the fertilization day. In experiment I, no differences were found (P>0.05) in cleavage rates (69 and 70%), blastocyst in D7 (37 and 38%) and blastocyst quality I (79 and 74%) in an atmosphere of 5% or 20%O2, respectively. The hatching rate in D9 considering all COC submitted to IVM was higher (P<0.05) for the 5%O2 group (21%) compared to the IVM and IVF group under 20%O2 (11%). A pregnancy rate of transferred embryos at 45 days (n=278) was similar (P=0.15) between treatments (25.8 e 33.6% for 5%O2 e 20%O2 ,respectively ). In experiment IIa blastocyst rates (51%) and quality I blastocysts (41%) in D7, was higher (P<0.05) in BSA+FCS group compared to the BSA group (42 and 30%), respectively. In experiment IIb, blastocyst rates were higher (P<0.05) in group BSA+FCS (47%) and similar between BSA (34%) and BSA+FCSD4 (43%) groups. Blastocyst rates quality I were higher (P<0.05) for groups BSA+FCS (34%) and BSA+FCSD4 (32%), compared to the BSA group (19.9%). A pregnancy rate of the transferred embryos (n=820) was similar between treatments in experiments IIa and IIb. Considering pregnancy rates corresponding only to IVM COC (Experiment IIa), the rates were higher (P<0.05) for the BSA+FCS group (16%) than the BSA group (12%). There was no detrimental effect in IVP of bovine embryos and their pregnancy rates when IVM, IVF and IVC were performed in 5%O2, 5%CO2 and 90%N2. IVP of bovine embryos is increased by the addition of 2% FCS to the IVC medium without any detrimental effect on their morphological quality and pregnancy rates. On the other hand, pregnancy rates related to IVM of COC incremented by the addition of 2% de Fc to the IVC medium SOFaaci+BSA.